Засоби номінації малих сукупностей в українській та іспанській мовах - Пелипенко, О.А. (Мовознавство, 2016)
У статті дається опис мовних засобів позначення малих сукупностей в українській та іспанській мовах на матеріалі художньої прози та періодики. Наводяться кількісні дані та аналізуються семантичні й лінгвістичні особливості вживання досліджуваної лексики. The article describes the linguistic means used in the works of Ukrainian and Hispanic prose writers and in the newspapers of Ukraine and Hispanic countries to describe small collections of people, creatures, objects and substances. The author provides statistics and description of peculiarities of usage of the vocabulary in consideration within the corpora of fiction and periodical publications for both languages.